Comparative statics for real options on oil: What stylized facts to use? - Diderik Lund; Ragnar Nymoen (University of Oslo, Department of Economics, 2013)
Comparative-statics results for financial options are often assumed to hold for real options. But the effects of higher volatility need not be increased value and postponed investment. This depends on signs of correlations and what parameters are held constant. For real options, the rate-of-return shortfall may change. The CAPM is commonly used to determine this. In contrast with widespread assumptions, the empirical analysis shows that the correlation of the returns on oil and the stock market is nonpositive and not invariant to changes in volatility. For crude oil during 1993-2008, these changes are identified as three significant breaks.
Keywords: D92; G13; G31; Q30; Q40; 330; real options; oil; volatility; CAPM; comparative statics